2018
DOI: 10.26444/aaem/75876
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of illness by women with breast cancer

Abstract: Introduction. Despite great progress in the diagnostics and treatment, breast cancer still remains the most frequently diagnosed malignant cancer in women. The outcomes of cancer treatment depend, to a considerable extent, on the degree of acceptance of the illness. The objective of the study was determination of the level of acceptance of the disease among the examined women with breast cancer. Materials and method. The study covered a group of 231 women who received treatment for breast cancer in the Rev. Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 15 publications
5
26
3
5
Order By: Relevance
“…Interestingly, the mean point value on the AIS among breast cancer patients in studies conducted by Polish authors was significantly higher than in our study [24,25]. A higher mean point value was also recorded among 117 patients on dialysis, with an average age of 29.5 years (25.32 points) in a study by Adamczuk et al [26].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Interestingly, the mean point value on the AIS among breast cancer patients in studies conducted by Polish authors was significantly higher than in our study [24,25]. A higher mean point value was also recorded among 117 patients on dialysis, with an average age of 29.5 years (25.32 points) in a study by Adamczuk et al [26].…”
Section: Discussioncontrasting
confidence: 68%
“…The older the patients, the lower the average level of illness acceptance. Cipora et al [25] and Sierakowska et al [31] demonstrated an identical correlation in their studies. Chrobak-Bień et al [27] and Staniszewska et al [33], however, did not find an effect of age on the acceptance of illness.…”
Section: Discussionmentioning
confidence: 53%
“…5 Women with breast cancer demonstrate moderate acceptance of their illness. 6,7 However, literature still lacks studies on the impact that acceptance of illness has on QoL in breast cancer patients. Thus, the aim of the study was to investigate the association between illness acceptance and quality of life (QoL) in patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, prevention and regular breast self-examination, which allows for an early detection of pathological changes, are an inseparably linked. 22 The individual case of a patient diagnosed with breast cancer used in this manuscript perfectly illustrates the essence of self-control. During breast self-examination, the patient detected a lump that turned out to be a malignant tumor at an early stage of development.…”
Section: Discussionmentioning
confidence: 91%
“…Thanks to quick diagnostics and an immediate treatment, the patient was qualified for a mammary gland-conserving therapy and successfully underwent a long and complicated treatment process. 21,22 Psychological problems in patients after tumor removal surgery are fear of relapse or the occurrence of metastases and fears associated with entering adjuvant treatment. These problems also result from the lack of knowledge.…”
Section: Discussionmentioning
confidence: 99%